Digitalisation challenges and opportunities for subnational governments - de Mello, Luiz (OECD Working Papers on Fiscal Federalism, 2020)
The world economy and societies are going through a digital transformation that goes well beyond computerisation and use of information and telecommunications technologies. This transformation is creating opportunities and challenges for all levels of government in the areas of tax and expenditure policy and administration, service delivery and fiscal-financial management, and regulatory practices and policies. However, governments (especially sub-national ones, SNGs) often also face shortages of skills, equipment and physical infrastructure, while having to address emerging challenges in cyber security risk management and data protection. The digital transformation calls for cooperation among the different layers of administration in support of effective and efficient digitalisation of SNGs. This paper reviews and discusses these opportunities and challenges